Industrial training report: Celestica Malaysia Sdn Bhd - Azizan, Muhammad Kameel (Universiti Teknologi MARA, Perlis, 2024)
Celestica Inc is a leading global provider of manufacturing services and supply chain solutions, primarily serving the technology industry. With headquarters in Toronto, Canada and operations spanning North America, Asia, Europe and South America. Celestica employs over 20,000 people worldwide. The company specializes in design, engineering, manufacturing and supply chain management across various sectors including aerospace, defense, communications, healthcare and industrial. Celestica is committed to innovation and sustainability, aiming to be the market leader in high reliability design, production and supply chain solutions. Key strengths include advanced technological infrastructure, a global network and a commitment to sustainability. However, challenges such as supply chain complexity and limited visibility pose significant risks. Opportunities for market expansion and supplier collaboration are significant while regulatory compliance and intense competition are major threats. To address these challenges and capitalize on opportunities, Celestica is advised to leverage technology for supply chain visibility, foster strategic partnerships and focus on sustainability and operational excellence. These strategies will enhance competitiveness and ensure long term success in the global market.